2009
DOI: 10.1038/emboj.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

SRBC/cavin-3 is a caveolin adapter protein that regulates caveolae function

Abstract: Caveolae are a major membrane domain common to most cells. One of the defining features of this domain is the protein caveolin. The exact function of caveolin, however, is not clear. One possible function is to attract adapter molecules to caveolae in a manner similar to how clathrin attracts molecules to coated pits. Here, we characterize a candidate adapter molecule called SRBC. SRBC binds PKCd and is a member of the STICK (substrates that interact with C-kinase) superfamily of PKC-binding proteins. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(165 citation statements)
references
References 49 publications
8
157
0
Order By: Relevance
“…We found that the purified scaffolding domain of caveolin1 that bound to cavin3 formed oligomers, as previously described (Fernandez et al, 2002), although we do not think that this is a requirement for cavin3 binding. This shows that cavin3 can bind to caveolin1 although it is not oligomerised into the characteristic larger assemblies of caveolae, which is in agreement with previous work showing that cavin3 is associated with caveolae following scission and most tightly associated with caveolin1 (McMahon et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found that the purified scaffolding domain of caveolin1 that bound to cavin3 formed oligomers, as previously described (Fernandez et al, 2002), although we do not think that this is a requirement for cavin3 binding. This shows that cavin3 can bind to caveolin1 although it is not oligomerised into the characteristic larger assemblies of caveolae, which is in agreement with previous work showing that cavin3 is associated with caveolae following scission and most tightly associated with caveolin1 (McMahon et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…In summary, we conclude that cavin3 is enriched at more deeply invaginated caveolae structures but that it is not required for the invagination of caveolae, which is in agreement with previous conclusions from cavin3 knock out mice (Hansen et al, 2013;Liu et al, 2014) Cavin3 and EHD2 control the equilibrium between stable and kiss-and-run types of caveolae at the cell surface Previous studies in knockout mice have shown that although cavin1 is required to form caveolae and cavin2 contributes to the invagination of caveolae, loss of cavin3 does not seem to affect caveolae morphology. Our data suggest that cavin3 acts at the later stages of deeply invaginated caveolae and previous studies has suggested that cavin3 effects caveolae trafficking (McMahon et al, 2009). To study whether cavin3 was involved in regulating the dynamics of caveolae at the cell surface, we used live-cell TIRF microscopy to visualise the behaviour of caveolae in caveolin1-GFP Flp-In TRex cells following small interfering RNA (siRNA)-mediated knockdown of cavin3 or EHD2 (Fig.…”
Section: Cavin3 Is Preferentially Associated With Deeply Invaginated supporting
confidence: 59%
See 1 more Smart Citation
“…However, the precise mechanisms by which cavins assemble with caveolins, especially in cardiac muscle, remain unclear. Moreover, the differing molecular composition of cavin complexes across cell types [e.g., cardiomyocytes express all cavin isoforms except for cavin 3 (22,48)] suggests that additional proteins contribute to caveolae formation and confer tissue-specific functions (49). For instance, EHD2, a member of the EHD family of endosomal recycling proteins (50) recently reported to regulate cardiac membrane protein targeting (51,52), has been shown to interact with cavin 1 and control the stability and turnover of caveolae (53).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, caveolae in adipocytes were suggested to produce TG (Ost et al 2005), which may also be transferred to LDs through the hemi-fusion channel. The functions of caveolins are closely linked to a family of cytoplasmic proteins termed cavins (Hill et al 2008;Bastiani et al 2009;Hansen et al 2009;McMahon et al 2009). PTRF/ cavin-1 is essential for the formation of caveolae (Hill et al 2008;Liu et al 2008) and, like caveolin, has been shown to be associated with LD function and lipid storage in cultured adipocytes (Aboulaich et al 2006), mice (Liu et al 2008), and human patients (Hayashi et al 2009;Rajab et al 2010).…”
Section: Interactions With Caveolae Caveolins and Cavinsmentioning
confidence: 99%